Batas Usia Perkawinan dan Perwalian: Pendekatan Komparatif antara Indonesia dan Negara Asia Tenggara Lainnya - Abdul Jamil (Sharia Journal and Education Center Publishing, 2024)
This paper examines the minimum marriage age and the concept of guardianship using a comparative approach between Indonesia and several Southeast Asian countries, including the Philippines, Malaysia, Brunei Darussalam, and Thailand. The primary focus is to analyze differences in minimum marriage age as stipulated by laws in each country and their implications on Islamic family law and national legislation. Additionally, the paper explores the social and health impacts of child marriages and legal protection measures for minors. The findings reveal significant variations in minimum marriage age across the region, influenced by local legal systems, traditions, and cultures. In Indonesia, the amendment of the minimum marriage age to 19 years for both males and females is seen as a progressive step in reducing child marriage rates and its adverse effects.